Model Berbasis Agen bagi Penyebaran Penyakit ISPA pada Musim Hujan di Bandung Selatan - Utomo, Dhanan Sarwo; Nuraeni, Shima; Putro, Utomo Sarjono (SBM ITB, 2012)
Since there was land conversion for urban development, South Bandung regency –especially Baleendah and Dayeuhkolot subdistricts– experiencing flood frequently. Noted as the worst flood for the last two decades, in the end of January 2010 water from the tributary of Citarum River inundate 4474 houses and force more than one thousand people to evacuate and stay in the temporary shelter for almost there months. With difficulties on accessing clean water, highly exposed to contaminated water and crowding in the temporary shelter, increasing the risk of infectious diseases. Diarrhea, Acute-Respiratory-Infections (ARI), and skin dieaseas are three most common diseases suffered by the refugees. But only ARI is the most sensitive because the infectivity includes human interaction. So, thispaper try to model the spread of ARI using agent-based modeling. Several scenarios –using diffent length of time and medicine stocks– are tested to monitor the number of refugees who get ARI or Pneumonia